Observations of sustainability practices in Malaysian research universities: highlighting particular strengths - Saadation, Omidreza; Salleh, Elias @ Ilias; Mohd Tahir, Osman; Dola, Kamariah (Universiti Putra Malaysia Press, 2009)
Although Sustainable Higher Education (SHE) is a very important issue in Malaysia, there have not been any comprehensive studies related to the current public Higher Education initiatives and efforts in sustainability. It is a relevant issue which merits a proper study to evaluate both the strengths and deficiencies of the local universities in terms of sustainability. Thus, to carry out this objective, an exploratory method was conducted by reviewing archival data, observation, interviews, as well as short and long conversations with both the staff and students of the four selected Malaysian research universities. The observation, interviews and conversations have validated the archival research. The results indicated that Malaysian research universities have already recognized the concept of SHE and embarked into the sustainability movement. However, there still remains a big gap towards achieving the idealistic goals. The findings would throw some insights into the existing policies and initiatives of SHE which could serve as a reference and preliminary study to improve the current situation.